Epigenetic dysregulation of interleukin 8 (CXCL8) hypersecretion in cystic fibrosis airway epithelial cells - Poghosyan, Anna; Patel, Jamie K.; Clifford, Rachel L.; Knox, Alan J. (Elsevier, 2016)
Airway epithelial cells in cystic fibrosis (CF) overexpress Interleukin 8 (CXCL8) through poorly defined mechanisms. CXCL8 transcription is dependent on coordinated binding of CCAAT/enhancer binding protein (C/EBP)β, nuclear factor (NF)-κB, and activator protein (AP)-1 to the promoter. Here we show abnormal epigenetic regulation is responsible for CXCL8 overexpression in CF cells. Under basal conditions CF cells had increased bromodomain (Brd)3 and Brd4 recruitment and enhanced NF-κB and C/EBPβ binding to the CXCL8 promoter compared to non-CF cells due to trimethylation of histone H3 at lysine 4 (H3K4me3) and DNA hypomethylation at CpG6. IL-1β increased NF-κB, C/EBPβ and Brd4 binding. Furthermore, inhibitors of bromodomain and extra-terminal domain family (BET) proteins reduced CXCL8 production in CF cells suggesting a therapeutic target for the BET pathway.